Comparative analysis of volatile and carotenoid metabolites and mineral elements in the flesh of 17 kiwifruit. Issue 7 (19th June 2021) - Zhang, Haipeng; Mo, Xiaoqin; Tang, Dongmei; Ma, Yuhua; Xie, Yunxia; Yang, Hongbin; Shi, Meiyan; Li, Lin; Li, Wenyun; Yan, Fuhua; Zhang, Yajuan; Zhang, Hongyan; et al.
Abstract : Abstract: Kiwifruit contains abundant nutritive compounds and is highly favored by the consumers worldwide. Therefore, detailed metabolic profiling is important to provide theoretic basis for the improvement of kiwifruit quality. In this study, the levels of volatiles, carotenoids, and mineral elements in the flesh of 17 kiwifruit accessions were evaluated. Acids and esters were the main volatiles in kiwifruit. During these 17 kiwifruit accessions, "Chenhong, " three "Jinyan, " and two "Guichang" germplasms were specifically rich in aromatic esters, which might be associated with their special taste. The main carotenoids were lutein, β‐carotene, and zeaxanthin, and their levels were also genotype specific, with the green‐fleshed "Guichang" having the highest level of carotenoids, and red‐fleshed "Fuhong" and "Chenhong" being rich in zeaxanthin. Partial correlation analysis showed that the contents of some mineral elements were significantly correlated with those of specific volatiles and carotenoids, indicating the impacts of mineral elements on the accumulation of volatiles and carotenoids in the kiwifruit flesh. These results indicated that the contents of carotenoids and volatiles seemed to be affected by mineral elements and also provided a new potential method for improving fruit flavor quality in production.